Perancangan Interior Lego Day Care Centre di Surabaya - Fransiscus Alvian Tanjaya; mariana wibowo (Intra, 2014)
With the increased economies of many working parents. As a result of normal family life becomes hampered, especially the attention to children - children that they need a day care. Day care centers are child care facilities are divided into groups that are usually performed during working hours. Facilities provided are a play area, study area, sleeping area, a library, cafeteria, office manager laundry, and soon. Concepts used in the interior design of Lego Day Care Centre in Surabaya is "Lego". Because Lego is one of the games favored by children - children and beneficial in helping to improve the child's motor performance of the sensor. And apply the shape and color that are characteristic of Lego into the design. Lego day care center is expected to help facilitate the development of children and parents who work.